A Review of Current State-Level Adverse Medical Event Reporting Practices Toward National Standards - Beckett, Megan K. (RAND Corporation, 2006)
Summarizes the results of a survey of a 50-state survey of systems for reporting adverse medical events that took place in 2004. The report documents the consistency of information that states collect, identifies issues relating to establishing a national patient safety repository, and presents a plan for implementing a standardized national system.